Metabolic Changes in the Myocardium during Adrenaline-Induced Injury and the Effect of Heart Cryoextract on Lactate-Pyruvate Metabolism - Mykola O. Chyzh; Fedir Vol. Hladkykh; Tetiana I. Liadova; Mariia S. Matvieienko; Roman R. Komorovsky (Ukrainian Journal of Cardiovascular Surgery, 2025)
Metabolic injury to the myocardium during excessive adrenergic stimulation is primarily mediated by overstimulation of β-adrenergic receptors, resulting in a cascade of biochemical and structural changes that lead to myocardial toxicity.Aim. To investigate the effect of an extract derived from cryopreserved fragments of piglet hearts on glycogenolysis activity in cardiomyocytes, and to evaluate its potential therapeutic efficacy in a model of adrenaline-induced myocardial dystrophy.Materials and methods. The study was conducted on 84 non-linear male white rats. Adrenaline-induced myocardial dystrophy was modeled using a single subcutaneous injection of 0.18 % adrenaline tartrate at a dose of 5 mg/kg (according to the method of Markova). The experimental group received an intraperitoneal injection of the extract (peptide concentration 0.1 mg/ml, 50 μg per 100 g body weight) daily for 14 days. LDH activity was measured in blood serum using a spectrophotometric method. Lactate and pyruvate concentrations were determined spectrophotometrically in myocardial tissue homogenates collected post-mortem.Results. In the untreated group, adrenaline administration caused significant metabolic disturbances: increased LDH activity, elevated lactate levels, and reduced pyruvate concentrations, indicating a shift toward anaerobic glycolysis and myocardial hypoxia. Administration of the extract significantly reduced LDH activity and lactate concentrations, while increasing pyruvate levels and restoring the lactate/pyruvate ratio toward physiological values. These findings suggest a restoration of oxidative phosphorylation and improved energy metabolism in cardiomyocytes.Conclusions. The extract of cryopreserved piglet heart tissue demonstrates therapeutic potential as a metabolic modulator in the context of catecholamine-induced myocardial injury. Its ability to normalize lactate-pyruvate metabolism indicates its promise as a cardioprotective agent for correcting metabolic imbalances in myocardial dystrophy.